Lymphomatoid papulosis – making sense of the alphabet soup: a proposal to simplify terminology. (2nd March 2017) - Kempf, Werner; Mitteldorf, Christina; Karai, Laszlo J.; Robson, Alistair
Summary: Clinically, lymphomatoid papulosis (LYP) is characterized by recurrent papulonodular lesions. Unlike this stereotypical clinical presentation, the histological spectrum of LYP is very wide, comprising distinct growth patterns, variably sized neoplastic cells, and different immunophenotypes. The revised 2016 WHO classification includes the histological LYP types A to E as well as another type characterized by a specific chromosomal alteration. In addition, new LYP types are going to be proposed, based not only on histological but also on clinical and genetic features. The ensuing expansion of the alphabetical list of histological types will add to the complexity of the terminology of LYP, thereby potentially increasing the risk of complicating rather than facilitating the diagnostic approach to the disease. Moreover, there may be overlap between individual disease types. This development raises the question as to how to simplify the terminology of LYP while still respecting its histological complexity. Herein, we advocate a practical approach to the terminology of LYP based on descriptive terms rather than the designation of LYP types by alphabetical characters. Our proposal aims to contribute to a pragmatic and user‐friendly approach, thus not only facilitating the diagnostic process but also the communication between clinicians and pathologists.